FOOD SAFETY TESTING OF FRESHWATER MUSSELS FROM DIFFERENT RIVER IN KAMPAR DISTRICT - Islami Hakim; Bustari Hasan; Sukirno Mus (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study aims to evaluate the content of heavy metals (Pb, Cd, Cu), Coliform and Fecal coliform in water and freshwater gravestones found in several in Kampar Regency. Of the several rivers in Kampar, three rivers were designated as research sites and from each river sampled by river and gravestone, the heavy metals Pb, Cd, Cu, Coliform and Fecal coliform were analyzed. The results of this study indicate the content of Pb, Cd, Cu in river water in a row on the river Dareh 0,000 mg / l, 0,0000 mg / l, 0,0346 mg / l, on the River Nail respectively 0,0065 mg / l, 0,0000 mg / l, 0.0392 mg / l, on the Kampar River 0.0326 mg / l, 0.0000 mg / l, 0.0365 mg / l. while on the gravestone shows the content of Pb, Cd, Cu on the Dareh River in succession 5 , 56 mg / kg, 0.20 mg / kg, 4.01 mg / kg, on the Paku River in a row 6.69 mg / kg, 0.23 mg / kg, 2.30 mg / kg, on the Kampar River in succession 3 , 95 mg / kg, 0.12 mg / kg, 3.61 mg / kg. Total Coliform and Fecal Coliform in water in the Dareh River 210 MPN / g and 160 MPN / g, on the Paku River> 1100 MPN / g and 1100 MPN / g, and on the Kampar River 210 MPN / g 290 MPN / g, on the gravestone in the Dareh River 210 MPN / g and 150 MPN / g, on the Paku River 1100 MPN / g and 1100 MPN / g, on the Kampar River 290 MPN / g and 290 MPN / g. Of the three rivers, it shows that the gravestone has been contaminated, especially Pb has passed the threshold for food safety, which is 1.5 mg / kg. The values and results of MPN of Coliform and Fecal coliform bacteria in gravestones also exceeded the threshold of 10 MPN / Keywords: Mussels, Plisbryoconcha exilis